Sustainable Performance of a Modular Building System Made of Built-Up Cold-Formed Steel Beams - Kajaharan Thirunavukkarasu; Elilarasi Kanthasamy; Perampalam Gatheeshgar; Keerthan Poologanathan; Heshachanaa Rajanayagam; Thadshajini Suntharalingam; Madhushan Dissanayake (Buildings, 2021)
Modular Building Systems (MBS) offer numerous benefits in terms of productivity, sustainability and safety. Therefore, MBSs are considered as a viable option to sort out the housing crisis in Britain as well as to drive Britain towards sustainable construction. Development in materials, manufacturing techniques, connection types and structural designs with respect to offsite construction is essential to achieve sustainable goals. Recent advancements in steel manufacturing, including Cold-Formed Steel (CFS), have showed potential benefits in structural performance compared to concrete and timber. Meanwhile, research was conducted to enhance the structural capacities of CFS sections by introducing different cross-sections, composite sections and techniques including optimization. Built-up sections were developed by connecting more than one channel section, and various research studies were conducted to assess their structural performances. However, sustainable performance of built-up sections in modular constructions is still unknown. Hence, this paper intends to develop an MBS using built-up sections for better sustainable performance. Literature review was carried out on the sustainability benefits of MBSs in terms of economic, environmental and social aspects. In addition to that, numerical analysis was performed to investigate the flexural capacity of built-up sections with different screw arrangements to address the sustainable aspects of modular construction by introducing novel sections. The numerical description, results and validations are also stated. Numerical results revealed that flexural capacities of built-up sections are improved up to 156% than those of single sections. Finally, the utilization of built-up sections in modular construction with sustainability enhancement is addressed and illustrated in a conceptual diagram.